THE SIGNIFICANCE OF INTERSTITIAL LYMPHOCYTOSIS IN RHEUMATIC DISEASE AND IN OTHER INFLAMMATORY PROCESSES - COSTERO, ISSAC CARLOS (INSTITUTO NACIONAL DE CARDIOLOGIA, CD. MEXICO, DF, MEX, 1947)
Summaries of other communications presented at the Second Inter-American Congress of Cardiology
AM HEART J
Keywords: SIGNIFICANCE, INTERSTITIAL, LYMPHOCYTOSIS, RHEUMATIC, DISEASE, INFLAMMATORY, PROCESSES; CIENCIAS MEDICAS; MEDICINA INTERNA; REUMATOLOGIA